Implikasi Putusan Mahkamah Konstitusi Nomor 77/PUU-IX/2011 Yang Menghapus Kewenangan Panitia Urusan Piutang Negara (PUPN) Terhadap Mekanisme Penyelesaian Utang Piutang Pada Bank BUMN/BUMD - Muhammad Yusni (SOSEK : Jurnal Sosial dan Ekonomi, 2022)
The company's business requires policies that are fast, sure, effective, and efficient because it is in accordance with the fundamental nature of the business itself. The Company Law has clearly regulated the corporate mechanism in accordance with the principles of good and healthy corporate governance. However, in practice in the field there is still discrimination between state/regional companies and private companies, especially banking companies. The problem discussed here is that although there has been a Constitutional Court Decision Number 77/PUU-IX/2011, there is still uncertainty and a long bureaucracy in the settlement of non-performing loans in state-owned/regional-owned banks and the risk of imposing anti-corruption laws. This is due to the strict implementation of the APBN/APBD mechanism. This normative juridical research concludes that the Constitutional Court's decision No. 77/PUU-IX/2011 which abolishes PUPN's authority over the PT debt settlement mechanism has implications for the process of settling debts and non-performing loans at state-owned/local-owned banks independently, more easily and efficiently. It no longer involves PUPN and the APBN/APBD mechanism. The position of BUMN/BUMD Banks is the same as private banks which are subject to the corporate mechanism based on the Company Law and the principles of sound corporate governance. It is hoped that with this decision of the Constitutional Court, the management of BUMN/BUMD Banks will be more free and independent in making breakthroughs and business expansion according to the company's goals and objectives. It is also hoped that all parties, especially the government as shareholder, must be committed and consistent with the implementation of existing regulations so that the business goals of state companies are maximized in increasing the company's business profits.